Monitoring of Technogenic Destructions of Oil and Gas Facili-ties using 3D Laser Scanning - Aleksandrovna Gubanova, Olga; Aleksandrovich Lovchikov, Vladimir; Vladimirovich Mironchev, Aleksey; Danilovich Cheshko, Iliya; Sergeevich Krutolapov, Alexander (International Journal of Engineering and Technology, 2018)
This article discusses application of 3D laser scanning aimed at assessment of consequences of destructions resulted from fires and other technogenic disasters of oil and gas facilities. Deformations of structures and equipment as a consequence of emergencies sometimes cannot be detected visually. It is required to apply modern instrumentation to determine deviations from designed parameters. In addition, after disasters it is required to determine the scope of loss and faults of equipment. Application of 3D laser scanning makes it possible to estimate both availability of buildings and equipment for further operation and the scope of destructions at complex engineering facilities of oil and gas industry. Laser scanning makes it possible to reduce significantly time required for examination and data processing in comparison with other measurement methods.Â Â Â